From Nasyid to Gambus: Discovering Spiritual Dimensions in Contemporary Indonesian Music Art - Al-Asyhar, Thobib (JURNAL AT-TURAS, 2023)
A lot of research has been conducted on the relationship between music and mysticism. However, most of the research focuses on the music and practices of Islamic mysticism in Turkey, South Asia, and Persia. There is some research on music in Indonesia, but the focus is more on youth preferences towards the genre of hadrah. This research aims to discuss aspects of spirituality, such as meaning, transcendence, to values in sufistic music in Indonesia. Using qualitative research methods with descriptive approaches, this study found that some of the Indonesian musical genres, ranging from nasyid, gambus, pop, and dangdut, have spiritual dimensions even though the music is not purely Islamic. The spiritual dimensions of such music vary, including meaning, values, transcendence, connectivity, and becoming, a manifestation of life that requires reflection and experience. These five spiritual dimensions are sometimes clearly written in lyrics, but sometimes obscurely contained in them. This research has theoretical implications that Sufistic music does not necessarily form music of the Islamic genre or music created by the Sufists; Sufistic music can be any genre of music to the extent it is judged to contain values or dimensions of the spirituality of Islamic Tasawuf itself.